2005
DOI: 10.1142/s0219061305000390
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Groups and Fields in Some Nonelementary Classes

Abstract: ABSTRACT. This paper is concerned with extensions of geometric stability theory to some nonelementary classes. We prove the following theorem:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…In 4.1, we present a notion of plane curve that works in our setting, in 4.2 we reformulate our group configuration theorem in terms of indiscernible arrays (Lemma 4.17), and finally in 4.3 we adopt Hrushovski's and Zilber's proof to our setting and show that a suitable plane curve can be used to find the group configuration. The work is continued in a forthcoming paper by the second author [20], where it is shown that an analogue for Zilber's trichotomy holds in a Zariski-like structure: a non locally modular Zariski-like structure interprets either an algebraically closed field or a non-classical group (see [16]). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 4.1, we present a notion of plane curve that works in our setting, in 4.2 we reformulate our group configuration theorem in terms of indiscernible arrays (Lemma 4.17), and finally in 4.3 we adopt Hrushovski's and Zilber's proof to our setting and show that a suitable plane curve can be used to find the group configuration. The work is continued in a forthcoming paper by the second author [20], where it is shown that an analogue for Zilber's trichotomy holds in a Zariski-like structure: a non locally modular Zariski-like structure interprets either an algebraically closed field or a non-classical group (see [16]). …”
Section: Introductionmentioning
confidence: 99%
“…A result like this would be in line with the existing studies of geometries in non-elementary cases. However, since the existence of a non-classical group (see [16] and [17] for locally modular cases) is still open, to prove something like this seems very difficult, and if it turns out that there are nonclassical groups, the playground is completely open. Another open question is whether B. Zilber's pseudo-exponentiation and quantum algebras (not at a root of unity) satisfy our axioms for Zariski-like geometries.…”
Section: Introductionmentioning
confidence: 99%
“…. , 0, c 1 +· · ·+c n −a+d) ∈ S. As above, it follows c 1 (ii)⇒(iii): By [6] (also in [1], these groups have been studied), there is a group (G, +) such that (a) Every member of G is a permutation of V .…”
Section: Subclaim 2221 F I Is Well-defined and Belongs To D(g A)mentioning
confidence: 89%
“…The problem we had in [2] was that we were not able to show that strongly minimal groups in M eq are abelian, see [5] and [6] for more on this problem in the general case. Thus at that time it looked as if the geometries could be wild.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation